Drug Utilization Evaluation and Impact of Pharmacist Interventions on Optimization of Piperacillin/Tazobactam Use: A Retrospective Analysis and Prospective Audit - Savera Arain; Fahad Khalawi; Sainul Abideen Parakkal; Hassan S. AlHamad; Shabeer Ali Thorakkattil; Faisal Fahad J. Alghashmari; Bader AlHarbi; Nujud Bakhashwain; Weaam Mustafa Alzawad; Ali AlHomoud (Antibiotics, 2023)
(1) Background: Piperacillin/tazobactam is a broad-spectrum antimicrobial encompassing most Gram-positive and Gram-negative aerobic and anaerobic bacteria. The inappropriate use of such broad-spectrum antibiotics is an important contributor to the rising rates of antimicrobial drug resistance worldwide. Drug utilization evaluation studies and pharmacists’ interventions are vital to assess, develop, and promote the rational use of antibiotics. This drug utilization study aimed to evaluate the current utilization practice of piperacillin/tazobactam in a hospital setting and assess the impact of pharmacist intervention in improving its appropriate use. (2) Methodology: In this study, we used a retrospective cohort and a prospective cohort, a cross-sectional, observational method. It included a retrospective (Cycle A/pre-intervention-CycA) phase followed by an educational interventional phase conducted by the pharmacists. During the 2 months of educational intervention, pharmacists used several methods, including workshops, lectures, oral presentations, and the development and reinforcement of clinical pathways to promote the judicious use of piperacillin/tazobactam. This was followed by a prospective (Cycle B/post-intervention-CycB) phase to improve piperacillin/tazobactam usage appropriateness. The appropriateness criteria for this drug utilization evaluation were established based on antimicrobial guidelines, the published literature, the institutional antibiogram, consultation from the antimicrobial stewardship committee, and the product monograph (Tazocin). The appropriateness of CycA and CycB patients was compared using the measurable elements, including indication and dose based on renal function, timely order for cultures, de-escalation, and use of extended infusion protocol. (3) Results: The study population comprised 100 patients in both CycA and CycB. The mean age of the patients was 66.28 ± 16.15 and 67.35 ± 17.98, and the ratios of men to women were found to be 49:51 and 61:39 in CycA and CycB, respectively. It was observed that inappropriate usage was high in CycA patients, and the appropriateness was improved in CycB patients. A total of 31% of inappropriate empirical broad-spectrum use was found in CycA, and it was reduced to 12% in CycB patients. The transition of appropriateness was observed in all measurable criteria, which includes the optimized dose according to the renal function (CycA = 49% to CycB = 94%), timely bacterial culture orders (CycA = 47% to CycB = 74%), prompt de-escalation (CycA = 31% to CycB = 53%), and adherence to extended infusion institutional guidelines (CycA = 34% to CycB = 86%). (4) Conclusions: The study highlighted important aspects of inappropriate piperacillin/tazobactam use. This can be considerably improved by proper education and timely interventions based on the pharmacists’ vigilant approach. The study results emphasized the need for surveillance of piperacillin/tazobactam usage by conducting similar drug utilization evaluations and practice to improve quality and safety in healthcare organizations globally.